2012
DOI: 10.1002/mmng.201200003
|View full text |Cite
|
Sign up to set email alerts
|

Redescription and phylogenetic relationships of Solenodonsaurus janenschi Broili, 1924, from the Late Carboniferous of Nýřany, Czech Republic

Abstract: The basal tetrapod Solenodonsaurus janenschi Broili, 1924, from Nýřany (Westphalian D, Late Carboniferous), Czech Republic, is redescribed and its phylogenetic position reevaluated. A distinct groove at the base of the maxillary teeth is regarded as an autapomorphic character, which is present in both the large and small specimens. Other characteristic features, which are not unique to S. janenschi, are: an extension of the lacrimal that forms the anteroventral margin of the orbit; a long posterior extension o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Even though Proterogyrinus was considered probably aquatic based on the presence of lateralline canals (although poorly developed) (Holmes, 1984), many temnospondyls thought to be semiaquatic, also possess these sensory sulci (see Schoch and Milner, 2000;Yates and Warren, 2000;Damiani, 2001). Nevertheless, the absence of sulci does not necessarily imply terrestriality (Vallin and Laurin, 2004, p. 68;Danto et al, 2012). The hypothesis that any stegocephalian with lateral-line sulci was amphibious rather than aquatic contradicts what we know of extant taxa (because the neuromasts of this organ do not support dehydration), unless we postulate that the sulci persisted in the adult even though the organ regressed and was lost, presumably at metamorphosis.…”
Section: Femur/tibia and Femur/pes Ratios Plots (Figure 12)mentioning
confidence: 99%
“…Even though Proterogyrinus was considered probably aquatic based on the presence of lateralline canals (although poorly developed) (Holmes, 1984), many temnospondyls thought to be semiaquatic, also possess these sensory sulci (see Schoch and Milner, 2000;Yates and Warren, 2000;Damiani, 2001). Nevertheless, the absence of sulci does not necessarily imply terrestriality (Vallin and Laurin, 2004, p. 68;Danto et al, 2012). The hypothesis that any stegocephalian with lateral-line sulci was amphibious rather than aquatic contradicts what we know of extant taxa (because the neuromasts of this organ do not support dehydration), unless we postulate that the sulci persisted in the adult even though the organ regressed and was lost, presumably at metamorphosis.…”
Section: Femur/tibia and Femur/pes Ratios Plots (Figure 12)mentioning
confidence: 99%
“…The ventral surface of the process shows a delicate sculpture of fine striations and pits. The morphology of the interclavicle is unique among anthracosauroids, as far as we can tell, but does bear some similarities with the interclavicles of Ichthyostega (Jarvik 1996), Westlothiana (Smithson et al 1994), possibly Solenodonsaurus janenschi (Carroll 1970;Laurin & Reisz 1999;Danto et al 2012), and especially seymouriamorphs such as Seymouria baylorensis (White 1939), Discosauriscus austriacus (Klembara & Bartík 2000), Utegenia shpinari (Klembara & Ruta 2004b), and Ariekanerpeton sigalovi (Klembara & Ruta 2005b). In several seymouriamorphs, in particular, the parasternal process is elongate and often with parallel sides, and merges into a fanshaped or rhomboid interclavicular plate.…”
Section: Appendicular Skeletonmentioning
confidence: 87%
“…Recent work has resulted in a slight shift in the established soft consensus on stegocephalian phylogeny, but to facilitate comparisons with the results of Laurin (), we reanalysed the data using our new methods on the same set of phylogenies, to better highlight the differences in results reflecting the methodological innovations introduced by Didier () and here (see below). In addition, we produced two new trees that reflect more recent analyses that place Solenodonsaurus either at the base of lepospondyls (Danto et al., ) or stemward of seymouriamorphs (Marjanović and Laurin, ). Other than that, only minor changes would need to be made to reflect the current consensus; recent research has confirmed that the trees used here still adequately represent the current views on early stegocephalian phylogeny (Marjanović and Laurin, ).…”
Section: New Empirical Study: Stegocephalian Body Size Evolution and mentioning
confidence: 99%
“…This yields 14 trees representing those previously used by Laurin (), on which our tests were carried out. In addition, we modified the variant of the main reference tree with 3 Ma minimal internal branch lengths and with Westlothiana as a basal amphibian (lepospondyl) by placing Solenodonsaurus closer to lepospondyls than to Westlothiana (Danto et al., ) or stemward of seymouriamorphs (Marjanović and Laurin, , ), which gave two more trees used only for analysis of cranial characters. This results in a total of 16 analyses tied to as many trees, which are presented in Appendix (and also present in Appendix ).…”
Section: New Empirical Study: Stegocephalian Body Size Evolution and mentioning
confidence: 99%